Influence of Gastric Emptying and Gut Transit Testing on Clinical Management Decisions in Suspected Gastroparesis. Issue 10 (October 2019) - Hasler, William L.; Rao, Satish S. C.; McCallum, Richard W.; Krause, Richard A.; Nguyen, Linda A.; Schulman, Michael I.; Lee, Allen A.; Moshiree, Baharak; Wo, John M.; Parkman, Henry P.; Sarosiek, Irene; Wilding, Gregory E.; et al.
Abstract : INTRODUCTION: Gastric emptying scintigraphy (GES) or wireless motility capsules (WMCs) can evaluate upper gastrointestinal symptoms in suspected gastroparesis; WMC tests can also investigate lower gut symptoms. We aimed to determine whether these tests impact treatment plans and needs for additional diagnostic evaluation. METHODS: In a prospective, multicenter study, 150 patients with gastroparesis symptoms simultaneously underwent GES and WMC testing. Based on these results, investigators devised management plans to recommend changes in medications, diet, and surgical therapies and order additional diagnostic tests. RESULTS: Treatment changes were recommended more often based on the WMC vs GES results (68% vs 48%) ( P < 0.0001). Ordering of additional test(s) was eliminated more often with WMC vs GES (71% vs 31%) ( P < 0.0001). Prokinetics ( P = 0.0007) and laxatives ( P < 0.0001) were recommended more often based on the WMC vs GES results. Recommendations for prokinetics and gastroparesis diets were higher and neuromodulators lower in subjects with delayed emptying on both tests (all P ⩽ 0.0006). Laxatives and additional motility tests were ordered more frequently for delayed compared with normal WMC colonic transit ( P ⩽ 0.02). Multiple motility tests were ordered more often on the basis of GES vs WMC findings ( P ⩽ 0.004). Antidumping diets and transit slowing medications were more commonly recommended for rapid WMC gastric emptying ( P ⩽ 0.03). DISCUSSION: WMC transit results promote medication changes and eliminate additional diagnostic testing more often than GES because of greater detection of delayed gastric emptying and profiling the entire gastrointestinal tract in patients with gastroparesis symptoms. TRANSLATIONAL IMPACT: Gastric scintigraphy and WMCs have differential impact on management decisions in suspected gastroparesis.